A Study of Carotid Intima Media Thickness Among Thalassemia Patient in HUSM - Samsudin, Ahmad Hadif Zaidin (2015)
Thalassemia patient lifespan nowadays has been increased significantly compared to previously due to the advancement of medical treatment and better healthcare system. As a result, more transfusion-related complications are seen, and one of the rising trends is the thromboembolic complication. Studies has shown that ultrasound measurement of carotid intima-media thickness (CIMT) can be used as a surrogate marker for future cardiovascular event and is recommended to be done in thalassemia patient as early diagnostic tool and for vascular risk stratification.